Proposed new interior design scheme for Hewlett Packard Retail Store at No: 39, Jalan Sultan Azlan Shah Utara, Taman Ipoh Selatan, 31400, Ipoh, Perak / Aainaa Mardhiah Roslee - Roslee, Aainaa Mardhiah (2008)
The final project of interior design for diploma is the manifestation to students' understanding on process aspects of interior design that has been studied from the basic to presentation level of design proposal. The chosen product for this project is Hewlett Packard (HP) retail shop, the proposed HP retail is at No.39, Jalan Sultan Azlan Shah Utara, Taman Ipoh Selatan, 31400, Ipoh, Perak. The reason that I chose HP as my project is because HP has just merged with Compaq in 2002 and since then, HP has been promoting it's product to the public market and expand their market from being the world's largest computer peripheral's vendor and hit the public market The purpose of this project is to expose HP to the new generation and help HP break through into the public market. In running this project, the most important issue is to set up a competitive retail than can measure up to the recent design. Plus, it is also to instill a more appealing design reflects HP. The research method for this project is based on observation on a few existing HP outlets around Kuala Lumpur and Ipoh and also a few of it's competitor's outlets like Apple and Sony. In conclusion, the new design cattery that will be run should have the characteristics and customers' needs besides the suitable concept to be shown. The design hopefully, will give benefits to all, either local or foreigner.